COMPARISON OF CONTINUOUS NON-INVASIVE ARTERIAL PRESSURE (CNAP) MONITORING VERSUS INTERMITTENT NON-INVASIVE BLOOD PRESSURE (NIBP) MONITORING FOR DETECTION OF HYPOTENSION DURING SPINAL ANAESTHESIA FOR ELECTIVE CAESAREAN SECTION (Asian Journal of Medical Research and Health Sciences, 2026)
Background and Aims: Hypotension following spinal anaesthesia for caesarean section is common and, if undetected, may compromise uteroplacental perfusion. Intermittent non-invasive blood pressure (NIBP) monitoring may miss or delay detection of hypotensive episodes. The continuous non-invasive arterial pressure (CNAP) monitor, based on the vascular unloading technique, provides beat-to-beat blood pressure values without arterial cannulation. We compared the ability of CNAP and intermittent oscillometric NIBP to detect hypotension during spinal anaesthesia for caesarean section. Methods: In this prospective, randomized, observer-blinded study, 50 healthy parturients of ASA physical status I–II undergoing elective caesarean section under spinal anaesthesia were monitored simultaneously with NIBP (every 1 minute until delivery, then every 3 minutes) and CNAP (continuous, recorded every 10 seconds until delivery) from the time of subarachnoid block until delivery of the baby. Clinical decisions regarding vasopressor and fluid therapy were based solely on NIBP readings. Incidence and time of detection of hypotension, systolic (SBP), diastolic (DBP) and mean arterial pressure (MAP) differences between the two techniques, side effects, and neonatal outcome (APGAR score, umbilical vein pH) were recorded. Results: The incidence of hypotension detected was 18% with NIBP compared with 78% with CNAP (p